2021
DOI: 10.1007/s10570-021-03794-x
|View full text |Cite
|
Sign up to set email alerts
|

Cotton nonwovens with unidirectional water-transport properties produced by atmospheric plasma deposition

Abstract: This is a repository copy of Cotton nonwovens with unidirectional water-transport properties produced by atmospheric plasma deposition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Pu et al [100] created a Janus fabric by plasma depositing hexamethyldisilane on the cotton nonwoven surface. While the surface of the untreated fabric exhibited hydrophilicity with a CA of 0 • degrees, the surface of the treated fabric exhibited superhydrophobicity (CA 150 • ), which was caused by the low-surface-energy substance hexamethyldisilane.…”
Section: Models In Exploratory Researchmentioning
confidence: 99%
“…Pu et al [100] created a Janus fabric by plasma depositing hexamethyldisilane on the cotton nonwoven surface. While the surface of the untreated fabric exhibited hydrophilicity with a CA of 0 • degrees, the surface of the treated fabric exhibited superhydrophobicity (CA 150 • ), which was caused by the low-surface-energy substance hexamethyldisilane.…”
Section: Models In Exploratory Researchmentioning
confidence: 99%
“…The chemical composition of the fabric was analyzed by FTIR (Figure h), which showed that compared to the original cotton fabric and hydrophobic coated area of the TR-MM fabric, the spectrum of the PDMAPS-coated area of the TR-MM fabric had obvious peaks corresponding to the carboxyl (C  O, 1738 cm –1 ) , and S  O (1240 cm –1 ) groups. , The peak at 800 cm –1 can be attributed to the Si–C in the coupling reagent TMSPMA. , …”
Section: Resultsmentioning
confidence: 99%
“…21,31 The peak at 800 cm −1 can be attributed to the Si−C in the coupling reagent TMSPMA. 32,33 2.2. Directional Water Transport and Thermoresponsive Properties of the Fabric.…”
Section: Resultsmentioning
confidence: 99%
“…It should be mentioned that the permeability, mechanical property, and abrasion resistance (up to 10,000 cycles) of the fabric were not affected by superhydrophobic finishing and plasma treatment. Recently, Pu et al [38] prepared a Janus fabric via plasma depositing HMDSO on the surface of cotton nonwoven fabric. The treated fabric surface showed superhydrophobicity with a contact angle (CA) of 150 • due to the HMDSO low-surface-energy material, and the untreated fabric surface showed hydrophilicity with CA of 0 • .…”
Section: Surface Modification 321 Plasma Treatmentmentioning
confidence: 99%